The relationship between fear of cancer recurrence and posttraumatic growth: a meta-analysis - Gu, Lianqi; Shen, Chen; Zhao, Linlin; Li, Na; Wang, Rao; Dai, Lili; Chu, Zhiping (Frontiers in Psychology, 2024)
Background: Theoretically, stress is positively correlated with posttraumatic growth (PTG).However, evidence for a correlation between fear of cancer recurrence (FCR), a cancer-specific stressor, and PTG is mixed. The present study aimed to systematically investigate the overall effect size between the two and to explore moderators that may influence this relationship.From the earliest available date to October 2023, a comprehensive search was conducted in seven databases. Correlation coefficients (r) were calculated using Stata software. Publication type, continent, trauma role, gender, FCR measurements, PTG measurements, sample size, age, and time since diagnosis were used to examine moderating effects. The National Heart, Lung, and Blood Institute's (NHLBI) assessment tool was used to evaluate study quality.Results: A total of 14 studies, involving 17 samples and 3701 participants, were included. The studies found a small association between FCR and PTG (r = 0.161, 95% CI: 0.070-0.249, p < 0.01) and large heterogeneity (I 2 = 85.5%). The strength of the association varied according to the publication type and FCR measurement.The current review suggests a small but significant positive correlation between FCR and PTG. Future studies would benefit from exploring additional moderators and the use of standardized, validated FCR measurement tools.